Considerations for Use of Pharmacodynamic Biomarkers to Support Biosimilar Development – (III) A Randomized Trial with Interferon Beta‐1a Products. Issue 2 (2nd December 2022) - Florian, Jeffry; Gershuny, Victoria; Sun, Qin; Schrieber, Sarah J.; Matta, Murali K.; Hazel, Anthony; Sheikhy, Morasa; Weaver, James L.; Hyland, Paula L.; Hsiao, Cheng‐Hui; Vegesna, Giri; DePalma, Ryan; et al.
Abstract : The US Food and Drug Administration (FDA) has taken steps to bring efficiency to the development of biosimilars, including establishing guidance for the use of pharmacokinetic and pharmacodynamic (PD) similarity study data without a comparative clinical study with efficacy end point(s). To better understand the potential role for PD biomarkers in biosimilar development and inform best practices for biomarker selection and analysis, we conducted a randomized, double‐blinded, placebo‐controlled, single‐dose, parallel‐arm clinical study in healthy participants. Eighty‐four healthy participants ( n  = 12 per dose arm) received either placebo or one of three doses of either interferon β‐1a (7.5–30 μg) or pegylated interferon β‐1a (31.25–125 μg) to evaluate the maximum change from baseline and the baseline‐adjusted area under the effect curve for the biomarkers neopterin in serum and myxovirus resistance protein 1 in blood. Both PD biomarkers increased following product administration with clear separation from baseline (neopterin: 3.4‐fold and 3.9‐fold increase for interferon β‐1a and pegylated interferon β‐1a, respectively; myxovirus resistance protein 1: 19.0‐fold and 47.2‐fold increase for interferon β‐1a and pegylated interferon β‐1a, respectively). The dose–response curves support that therapeutic doses were adequately sensitive to detect differences in both PD biomarkers for consideration in a PD similarity study design. Because baseline levels of both biomarkers are low compared with on‐treatment values, there was little difference in using PD measures adjusted to baseline compared with the results without baseline adjustment. This study illustrates potential methodologies for evaluating PD biomarkers and an approach to address information gaps when limited information is publicly available for one or more PD biomarkers.